Implementasi Program Merdeka Belajar Kampus Merdeka di Era Digital dalam Menciptakan Karakter Mahasiswa Hukum yang Berkarakter dan Profesional: Implementation of the ’Merdeka Belajar Kampus Merdeka’ Program in the Digital Era in Creating Character and Professional Law Students - Rodiyah, Rodiyah (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Merdeka Belajar Kampus Merdeka Program (MKBKM) launched by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia is one of the breakthroughs in the digitalization era in the education sector. This program enables student exchange and also opens the boundaries of (physical) classrooms into digital spaces. This study aims to analyze the implementation of the MBKM program at the Faculty of Law, State University of Semarang in supporting the vision and mission of the UNNES Faculty of Law. In addition, this study aims to analyze the various obstacles faced during the implementation of the program and their relation in shaping the character of law students who are professional and character.